Modern Literary Prekmurian Language: the Case of Porabje - Kowalski, Paweł (Poznańskie Studia Slawistyczne, 2015)
The aim of the paper is to present the modern Prekmurian language that is nowadays used in Porabje. Porabje, located in Hungary, is a part of the bigger historical region named Prekmurje. While the Prekmurje was divided between Jugoslavia and Hungary after the first world war, one could see that the role of the Prekmurian language in Porabje was marginalized. Now it is used only in a few language areas. The consideration leads to some terminological conclusions.